Accelerating Growth Through Strong HR Practices and Robust Governance - Rohatgi, Nitish Kumar; Verma, Prakash Kumar (Wisdom Journal of Humanities and Social Sciences, 2024)
The article "Economic Milestones: Driving Growth Through HR Practices and Good Governance" examines the significance of HR practices and good governance in promoting economic development. This statement emphasises the combined influence of strategic human resource management and governance principles on fostering development, and highlights their interdependence with organisational success. The article explores the impact of well defined human resources processes on employee engagement, professional development, and the innovation and efficiency of a company. Emphasising the need of connecting HR strategy with larger company goals is crucial, as it fosters a collaborative endeavour that drives financial success. The success and longevity of companies in dynamic economic environments are significantly impacted by their methods for recruiting, cultivating, and retaining talent. Moreover, the article emphasises that strong leadership is essential for maintaining economic progress. This article discusses how accountable and transparent governance systems may create a favourable environment for investment, enhance economic stability, and attract both local and foreign capital. This research investigates the correlation between ethical leadership and economic success, highlighting the crucial role of organisations that prioritise integrity and responsibility in driving social and financial advancement. The study finishes by emphasising that achieving economic benchmarks requires a cohesive approach to human resources practices and governance principles. Organisations may achieve long-term success and have a significant impact on the economy by effectively using their workers’ strengths while upholding ethical governance norms.